2011
DOI: 10.1002/anie.201002094
|View full text |Cite
|
Sign up to set email alerts
|

Sweet and Umami Taste: Natural Products, Their Chemosensory Targets, and Beyond

Abstract: Much of our appreciation of food is due to the excitement of the perception of "sweet" and "umami" taste. With a special focus on natural products, this Review gives a summary of compounds that elicit and modulate "sweet" or "umami" taste responses. It will be discussed how the interaction of these molecules with the oral sweet and umami taste receptors stimulates receptor cells to secrete neurotransmitters to induce neural activity that is conveyed to the cerebral cortex to represent sweet and umami taste, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
154
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 198 publications
(308 reference statements)
6
154
0
2
Order By: Relevance
“…that interacts with the ATD of hT1R2 (12). As expected, mT1R2-mT1R3 did not respond to acidic stimulation after MCL preincubation, whereas hT1R2-hT1R3 did (Fig.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…that interacts with the ATD of hT1R2 (12). As expected, mT1R2-mT1R3 did not respond to acidic stimulation after MCL preincubation, whereas hT1R2-hT1R3 did (Fig.…”
Section: Resultssupporting
confidence: 74%
“…It has been reported that the acid-induced sweetness of MCL is diminished by a sweet taste inhibitor, lactisole (11), which inhibits hT1R2-hT1R3 by interacting with the transmembrane domain (TMD) of the hT1R3 subunit (12). This finding strongly indicates that MCL acts through the hT1R2-hT1R3.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations